Character building peserta didik melalui pembiasaan kegiatan keagamaan dalam upaya membentuk kepedulian sosial - Royani, Siti Ida; Laila, Azza Nor (Al-Liqo: Jurnal Pendidikan Islam, 2024)
Habits that prioritize one's own personality can influence all behavior that is not in line with character where education prioritizes an attitude of togetherness. If it is related to children's education now, they must be taught good habits to minimize inappropriate views. This research aims to examine the role of religious activities in the form of social care character of students at Madrasah Tsanawiyah Hasyim Asy'ari Kalipucang Wetan. This research uses a qualitative descriptive method with a field approach, where data is collected through observation, interviews and documentation. The research results show that religious activities are implemented through three main programs: first, through self-development, which includes reading al-barzanji, Islamic speech competitions, and reciting the yellow book; second, from subjects that include tahfidz juz 30 as well as worship practices such as ablution, prayer, and tahlil; third, with the existence of school culture such as reading Asmaul Husna, congregational prayers, and almsgiving activities. The formation of students' social care character is carried out through habituation, example and guidance by teachers.